John Birks: Pioneer in quantitative palaeoecology. (January 2015) - Battarbee, Richard W; Lamb, Henry; Bennett, Keith; Edwards, Mary; Bjune, Anne E; Kaland, Peter E; Berglund, Björn E; Lotter, André F; Seppä, Heikki; Willis, Kathy J; Herzschuh, Ulrike; Birks, Hilary H
We describe the career of John Birks as a pioneering scientist who has, over a career spanning five decades, transformed palaeoecology from a largely descriptive to a rigorous quantitative science relevant to contemporary questions in ecology and environmental change. We review his influence on students and colleagues not only at Cambridge and Bergen Universities, his places of primary employment, but also on individuals and research groups in Europe and North America. We also introduce the collection of papers that we have assembled in his honour. The papers are written by his former students and close colleagues and span many of the areas of palaeoecology to which John himself has made major contributions. These include the relationship between ecology and palaeoecology, late-glacial and Holocene palaeoecology, ecological succession, climate change and vegetation history, the role of palaeoecological techniques in reconstructing and understanding the impact of human activity on terrestrial and freshwater ecosystems and numerical analysis of multivariate palaeoecological data.